Ecologistes des villes et écologistes des champs : analyse spatiale de l’implantation en France des partis écologistes et «Chasse Pêche Nature et Traditions» - Michel Bussi; Loïc Ravenel (Cybergeo, 2001)
According to the classification of S.Rokkan, four divisions have generated political parties in democracies : church/secular, center/periphery, owners/workers and rural/urban divisions. The rural/urban division is the most recent and has produced fewer parties than the other divisions. Nevertheless, the growth of green parties is sometimes associated to electoral urban structuration and we can suppose that the apparition of an agrarian party in France («Chasse, Pêche, Nature et Tradition») is related to a rural structuration. To test the hypothesis of the influence of urbanisation on the localisation of «les Verts» and «CNPT», we’ll use spatial analysis methodology at two different scales: France by «canton» and Basse-Normandie by «commune». Our goal is to illustrate the actual electoral realignment in occidental democracies  (both decline of the great parties and the class vote, relative decrease of the «left wing/right wing» division, votes on particular stakes) and to demonstrate that these changes are produced by new spatial patterns.